Factors affecting estrus and fertility of Holstein heifers after prostaglandin F2α - Stevenson, Jeffrey S.; Schmidt, M.K.; Call, Edward P. (Kansas Agricultural Experiment Station, 2012)
Stage of the estrous cycle, time of insemination, and season of the year were examined for their influence on estrus and fertility of 223 Holstein heifers after prostaglandin F2α(PGF). Heifers given PGF early in the estrous cycle (days 5 to 8 where estrus = day 0) had shorter intervals (by 11 hr) to heat than heifers given PGF later in the cycle (days 14 to 16). Heats also were more closely synchronized for heifers treated early in the cycle. Season of the year had no effects on the interval to estrus or on proportion of heifers observed in heat. Conception rates were highest when heifers were bred after estrous detection. Inseminations by appointment at 80 hr after PGF reduced conception for heifers treated early in their estrous cycles. Variability of intervals to estrus can reduce fertility, if heifers are only bred at 80 hr after PGF without regard to when estrus occurred.
Keywords: Dairy; Prostaglandin F2-alpha; Estrous cycle; Fertility; Conception rate